On the structure of an aqueous propylene glycol solution. - Rhys, N; Gillams, R; Collins, L; Callear, S; Lawrence, M; McLain, S (American Institute of Physics, 2016)
Using a combination of neutron diffraction and EPSR computational modelling, the interactions in a 30 mol% aqueous solution of propylene glycol (PG), which govern both the hydration and association of this molecule in solution, have been assessed. From this work it appears that PG is readily hydrated, where the most prevalent hydration interactions were found to be through both the PG hydroxyl groups but also alkyl groups typically considered hydrophobic. Hydration interactions of PG dominate the solution, over PG self-self interactions and there is no evidence of more extensive association. This hydration behavior for PG in solutions suggest that the preference of PG to be hydrated rather than self associate may translate into a preference for PG to bind to lipids rather than itself, providing a potential explanation for how PG is able to enhance the apparent solubility of drug molecules in vivo.